Discrepancies between self‐reported tick bites and evidence of tick‐borne disease exposure among nomadic Mongolian herders. (10th April 2019) - Lkhagvatseren, Sukhbaatar; Hogan, Kathryn M.; Boldbaatar, Bazartseren; von Fricken, Michael E.; Anderson, Benjamin D.; Pulscher, Laura A.; Caddell, Luke; Nymadawa, Pagbajabyn; Gray, Gregory C.
Abstract: Twenty‐six per cent of Mongolians live pastoral lifestyles, increasing their likelihood of exposure to ticks and placing them at a higher risk for contracting tick‐borne diseases (TBDs). Anaplasma spp. and Rickettsia spp. have been identified in ticks, livestock and humans in Mongolia, but no known qualitative research has been conducted investigating the association between nomadic herder characteristics, tick bite history and exposure to TBDs. To better understand the association between self‐reported tick bites and symptoms versus actual exposure to TBDs, this study paired serological data with 335 surveys administered to Mongolian herders, ages 12–69, from 2014 to 2015. Logistic regression results identified no significant associations between reported tick bites or symptoms with serological evidence of Anaplasma spp. and Rickettsia spp. controlling for age, gender and aimag. Among the 335 respondents who were seropositive to either Anaplasma spp. or Rickettsia spp., 32.9% self‐reported experiencing abnormal symptoms such as redness, inflammation, headache, arthritis or fever after being bitten. Alternatively, 17.3% (58/335) of individuals reported experiencing symptoms following a tick bite in instances where serological results indicated no exposure to Anaplasma spp. or Rickettsia spp. Results also identified inconsistencies in reporting and seroprevalence among different age groups, with children having the highest reporting and treatment seeking rates but low levels of exposure in comparison with other groups. While survey results showed that individuals were aware of peak tick seasons and tick species that inhabit specific areas, 58% of heads of households (49/84) were unaware that ticks can cause disease in livestock or dogs. This study suggests that herders are an at‐risk population in Mongolia with gaps in awareness of TBD risk. Increased surveillance paired with focused outreach to prevent TBDs targeted to the herder population is encouraged.